2011
DOI: 10.1103/physreva.84.063604
|View full text |Cite
|
Sign up to set email alerts
|

Vortices in spin-orbit-coupled Bose-Einstein condensates

Abstract: Realistic methods to create vortices in spin-orbit-coupled Bose-Einstein condensates are discussed. It is shown that, contrary to common intuition, rotation of the trap containing a spin-orbit condensate does not lead to an equilibrium state with static vortex structures, but gives rise instead to non-equilibrium behavior described by an intrinsically time-dependent Hamiltonian. We propose here the following alternative methods to induce thermodynamically stable static vortex configurations: (1) to rotate both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 63 publications
(122 reference statements)
4
149
3
1
Order By: Relevance
“…For SO coupled bosons, many questions remain open. Recently several works begin to address the questions about the superfluid critical velocity 42 , vortices in presence of external rotation 47,48,49 , the effects of dipolar interactions 50 , the collective modes 51 , superfluid to Mott insulator transition in a lattice 52 , the interplay between magnetic field and SO coupling 53 , and the dynamical effects nearby Dirac point due to SO coupling 54,55,56 . The research along this direction will definitely reveal more interesting physics and stimulate more interesting experiments.…”
Section: Spin-orbit Coupled Quantum Gasesmentioning
confidence: 99%
“…For SO coupled bosons, many questions remain open. Recently several works begin to address the questions about the superfluid critical velocity 42 , vortices in presence of external rotation 47,48,49 , the effects of dipolar interactions 50 , the collective modes 51 , superfluid to Mott insulator transition in a lattice 52 , the interplay between magnetic field and SO coupling 53 , and the dynamical effects nearby Dirac point due to SO coupling 54,55,56 . The research along this direction will definitely reveal more interesting physics and stimulate more interesting experiments.…”
Section: Spin-orbit Coupled Quantum Gasesmentioning
confidence: 99%
“…Different studies have revealed the existence of a "stripe phase" (consisting of a linear combination of plane waves) [6] and phase transitions between it and states with a single plane wave or with zero momentum [7]. The existence of topological structures, such as vortices with [8] or without [9] rotation, Skyrmions [10] and Dirac monopoles [11], as well as self-trapped states (solitons) of an effective nonlinear Dirac equation (NLDE), was also illustrated [12]. While the above studies refer to BECs with repulsive interactions, to the best of our knowledge, SO-coupled BECs with attractive interactions have not been studied so far.…”
mentioning
confidence: 99%
“…In applications, the principal direction of the condensate (or equally the momentum of condensate wave function) can be controlled by applying an infinitesimal magnetic field or a shift of the wavelength of the vector light coupled with the hyperfine states of ultracold atoms [26,57]. The momenta of the excitations over the condensate due to the motion of the impurity at v/λ = 0.1 for the θ0 in (a).…”
Section: B Impurity Valvementioning
confidence: 99%
“…It provides physicists with a new platform to study the effects of SOC in many-body systems. A plenty of researches have been done on the properties of the BEC with SOC, including the groundstate phase [14][15][16][17][18][19], fluctuations above the ground state [20][21][22][23], and spin-orbit coupled BECs with other coldatom techniques, such as dipole-dipole interactions, optical lattice and rotating trap [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%